Perseverance - Whittall, Chuck (Ascent Audio, 2021)
A chronological blueprint of Chuck Whittall's adversities and successes that outlines a plan for how to build a billion-dollar business. Through his own story of hardship and triumph, Chuck Whittall shares the principles he used to overcome obstacles that can derail a business. In Perseverance: Broke to Billions, Whittall details what he's learned-from making key decisions and raising capital, to overcoming financial deficits and evaluating prospective opportunities.
Online resource; Title from title page (viewed February 9, 2021)
Keywords: Audiobooks; Livres audio